ANALYSIS OF RISK FACTORS RELATED TO CORONER HEART DISEASE IN ONE OF THE INDONESIAN NATIONAL HOSPITALS - RisdaHidayanti, Fatma; R., PrabaDiyan; Bakar S, Abu (International Journal of Psychosocial Rehabilitation, 2020)
Background: Coronary heart disease (CHD) is one of the greatest causes of death in developing countries. This disease is associated with both uncontrollable and uncontrollable risk factors. Controllable risk factors can be used as an effort to prevent CHD risk.Aim: This study aimed to investigate the dominant risk factors that trigger Coronary Heart Disease (CHD) in a national hospital in Central Java province, Indonesia.Method: This study was a descriptive analysis with a cross-sectional approach. The dependent variable was CHD, and the independent variables were CHD risk factors, namely age, sex, dyslipidemia, hypertension, smoking, diabetes mellitus (DM), stress, and obesity. The sampling technique was purposive sampling with the number of respondents of 49 patients with CHD and 49 patients without CHD, who were treated at Dr Moewardi Hospital Surakarta. The data used in this study was primary data from the stress and smoking questionnaire and secondary data from a medical record. The statistical test used was logistic regression analysis.Results: Based on the results of this study, all respondents with CHD were triggered by age factors over 40 years (45.92%) with a medical history of respondents experiencing dyslipidemia (31%), hypertension (33%), and diabetes mellitus (22.45%). Whereas gender factors, obesity, family history, stress, and smoking had a minor influence on CHD. However, the odds ratio through multivariate logistic regression analysis (1.5 to 2.9) showed sufficient values can trigger CHD.Conclusion: It can be concluded that the age factor, dyslipidemia, hypertension, and diabetes mellitus were the dominant factors in coronary heart disease in a national hospital in Indonesia. Whereas gender factors, obesity, family history, stress, and smoking had a minor influence that can trigger CHD.